Predictive Value of Thyroglobulin Changes for the Curative Effect of Radioiodine Therapy in Patients With Metastatic Differentiated Thyroid Carcinoma - Wang, Congcong; Zhang, Ruiguo; Wang, Renfei; Meng, Zhaowei; Zhang, Guizhi; Dong, Feng; He, Yajing; Tan, Jian (Frontiers in Endocrinology, 2021)
Abstract Background: Serum thyroglobulin (Tg) serves as a sensitive and easily available tumor marker for patients with metastatic differentiated thyroid carcinoma (m-DTC). The aim of the present study was to evaluate the predictive value of suppressed Tg changes (Δsup-Tg) and /or stimulated Tg changes (Δsti-Tg) to evaluate the efficacy of radioiodine therapy (RT). Methods: We studied 117 patients with m-DTC who received RT. Δsup-Tg and Δsti-Tg were compared after the first RT in different therapeutic response groups and a receiver-operating characteristic (ROC) curve was used to determine the cut-off values to predict non-remission. Univariate and multivariate analyses were used to investigate the effects of 17 observed factors on the efficacy of RT. Results: A total of 218 RT events in 117 patients with m-DTC were analyzed. After the last RT, the remission rate was 70.94% (83/117), and the proportion of remission events accounted for 74.77% (163/218). ROC curve analysis showed that the cut-off values for Δsup-Tg and Δsti-Tg after the first RT to predict the non-remission of RT were 21.54% and 27.63%, respectively. Age, the size of the metastasis, the maximum count of target metastatic lesions and the average count of contralateral non-target tissue on tomographic imaging (Tmax/NTmean) of the first RT, and Δsup-Tg after the first RT were identified as independent factors associated with RT efficacy. Conclusions: Tg response was valuable to predict RT efficacy for patients with m-DTC. Age, the size of the metastasis, Tmax/NTmean, and Δsup-Tg after the first RT were verified as independent predictive factors of RT efficacy.